Pengembangan Flipbook Berbasis Majalah dalam Pembelajaran Menulis Ilmiah - Izhatullaili Izhatullaili; Ilmatus Sadiyah (Jurnal Pendidikan dan Sastra Inggris, 2025)
Scientific writing is a critical skill for university students, both for academic success and personal development through writing competitions. However, many students struggle with structuring scientific papers, applying analytical techniques, and navigating the publication process. These challenges are often caused by limited scientific literacy and can delay academic progress, particularly the completion of final projects or theses. To address this issue, a training program using a digital flipbook in magazine format was conducted at the Primary School Teacher Education Program of Universitas Nusa Cendana. The program aimed to enhance students' writing competence and digital literacy through accessible, engaging learning media. The program involved 41 students and included pre- and post-tests, training on scientific writing principles, practical exercises, and interactive discussions. The flipbook, accessible via mobile devices, offered structured guidance and visual appeal, making it easier for students to revisit and understand the content. Results indicated significant improvements in students’ understanding and motivation. More than 85% of participants rated the flipbook positively in terms of readability, content clarity, and design. The digital format not only facilitated flexible learning but also encouraged consistent engagement with scientific writing practices.